Contour Integration in Dynamic Scenes: Impaired Detection Performance in Extended Presentations - Grzymisch, Axel; Grimsen, Cathleen; Ernst, Udo A. (Frontiers in Psychology, 2017)
4 Since scenes in nature are highly dynamic, perception requires an on-going and robust 5 integration of local information into global representations. In vision, contour integration (CI) 6 is one of these tasks, and it is performed by our brain in a seemingly effortless manner. 7 Following the rule of good continuation, oriented line segments are linked into contour percepts, 8 thus supporting important visual computations such as the detection of object boundaries. 9 This process has been studied almost exclusively using static stimuli, raising the question of 10 whether the observed robustness and “pop-out” quality of CI carries over to dynamic scenes. 11 We investigate contour detection in dynamic stimuli where targets appear at random times by 12 Gabor elements aligning themselves to form contours. In briefly presented displays (230ms), 13 a situation comparable to classical paradigms in CI, performance is about 87%. Surprisingly, 14 we find that detection performance decreases to 67% in extended presentations (about 1.9- 15 3.8s) for the same target stimuli. In order to observe the same reduction with briefly presented 16 stimuli, presentation time has to be drastically decreased to intervals as short as 50ms. Cueing a 17 specific contour position or shape helps in partially compensating this deterioration, and only in 18 extended presentations combining a location and a shape cue was more efficient than providing 19 a single cue. Our findings challenge the notion of CI as a mainly stimulus-driven process leading 20 to pop-out percepts, indicating that top-down processes play a much larger role in supporting 21 fundamental integration processes in dynamic scenes than previously thought.